The Effect of Pin Profiles and Process Parameters on Temperature and Tensile Strength in Friction Stir Welding of AL6061 Alloy - Emamian, S. (Pleiades Publishing, 2019)
The main source of the heat generation during the Friction Stir Welding (FSW) is the friction force between tool and workpiece and the plastic deformation. The geometry of the tool including the pin and the shoulder highly affects the friction force. In this study, the effects of different pin profiles with different rotational and traversing speed are evaluated in order to obtain the optimum pin profile using heat generation and tensile strength. Three different rotational speed and welding speeds are applied with threaded cylindrical, conical, stepped conical and square pin profiles. Thermocouples K type have been embedded in order to record the temperature during the welding at the advancing and the retreating side. Moreover, tensile test and microstructure analysis are performed in order to study the microstructure. The results of experimental process and design of experiments are correlated well. The better joint produced with threaded cylindrical tool pin profile with rotation speed of 1600 rpm and welding speed of 40 mm/min. Â© 2019, Springer Nature Singapore Pte Ltd.